If it's not what You are looking for type in the equation solver your own equation and let us solve it.
c+3=3(11-3c)
We simplify the equation to the form, which is simple to understand
c+3=3(11-3c)
Reorder the terms in parentheses
c+3=+(+33-9c)
Remove unnecessary parentheses
+c+3=+33-9c
We move all terms containing c to the left and all other terms to the right.
+1c+9c=+33-3
We simplify left and right side of the equation.
+10c=+30
We divide both sides of the equation by 10 to get c.
c=3
| 6.1=u-3.3 | | x+5y=4z | | 1/2(1/4) | | -9x-6=6x+9 | | 5/4t=10 | | -24=3/4j | | 2.5=g-7 | | (x+5)(x+5)-(x-3)(x+5)= | | 25/4*5/2 | | 15/a=-10 | | 3e+1=e+1 | | 2x+3=9x-1+x | | 2m+5=25+6m | | 7.2=y-6 | | 4x+17=4-7x | | 1/4h+9=-1/2h-11 | | 7.41=n-9.59 | | (3*62)-25+n=166 | | (2x+3)(3x+7)=0 | | 7x-13=2x-3 | | y=4x+160 | | 12x+10y=202 | | 3x+20=8-x | | -80=4x-16+4 | | 5/6p=20 | | f/-7-8=2 | | 11x-7=5x-13 | | 5z+5=2(8z-3) | | 22-3x=4x | | 4y-4=7(y-1) | | x(x-0.05)=300 | | -10+4w+6=-2w+23-3w |